Choices & change : macroeconomics. - Harrison, Ken (Producer and director); Harrison, Ken (Producer and director); Owens, Katherine (Academic Video Online, 2000)
This Part 5 of Lesson 2, Confronting Scarcity is about comparative advantage of countries like United States and Brazil in which they benefit from international trade.